Kombinasi Penerapan Teknik Relaksasi NASON (Nafas Dalam dan Benson) Terhadap Skala Nyeri Pada Pasien Ulkus Diabetik - Novita Putri Wulandari; Julvainda Eka Priya Utama (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Diabetes mellitus is a group of metabolic diseases characterized by high blood sugar levels due to abnormalities in insulin secretion, insulin action, or both. Neuropathic ulcers should be regularly debrided. Debridement is a way of cleaning diabetic ulcers that involves controlling the moisture in the wound. When removing necrotic tissue, the client feels pain. Efforts to overcome pain can be made with non-pharmacological therapy, with the NASON relaxation technique, namely the effort of taking deep breaths and repeating ritual phrases repeatedly, which is the best way to relieve pain, where the body naturally releases endorphin hormones. Objectives: to determine the effect of NASON treatment on pain scores in patients with diabetic ulcers. Methods: This research applies a quantitative approach using the cross-sectional method. The application of the total sampling technique resulted in a sample size of 50 people. Data analysis is done through univariate and bivariate analysis. Results: This type of research is quantitative. The study population consisted of patients receiving treatment for diabetic ulcers. The sampling technique in this purposive sampling with a total of 30 participants. Discussion: Administration of NASON relaxation therapy has an effect on the pain scale in diabetic ulcers.